Politics and Force Levels : The Strategic Missile Program of the Kennedy Administration. - Ball, Desmond (Berkeley : University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1980.
Description based upon print version of record.
JSTOR
Keywords: United States -- Military policy; Strategic forces -- United States; Intercontinental ballistic missiles; United States -- Politics and government -- 1961-1963.